The role of 18F-FDG PET/CT in diagnosing cardiac infiltration and therapeutic evaluation in extranodal nasal-type NK/T-cell lymphoma: a case report - Liao, Taiping; Li, Lingxiao; Fu, Guoxu; Li, Li; Qi, Qinlin; Long, Yongjun (Frontiers in Oncology, 2025)
Extranodal nasal-type NK/T-cell lymphoma is closely associated with Epstein-Barr virus (EBV) infection and primarily involves the nasopharynx. We report a rare case of extranodal nasal-type NK/T-cell lymphoma with widespread lymphomatous infiltration, including cardiac involvement, an exceedingly uncommon manifestation. This case emphasizes the pivotal role of18F-FDG PET/CT in diagnosing and evaluating treatment outcomes in extranodal nasal-type NK/T-cell lymphoma